FOLKLOR CIREBON DALAM LUKISAN KELUARGA SENIMAN: Komparasi Visual Karya Haryadi Suadi dan Radi Arwinda - Pertiwi, Annisa Bela (2012)
Painting is the result of creative work, intention, and sense of human sight which's can be seen by human vision. A painting isn't loose from the creator "the painter". Some of artist in Indonesia still take the traditional themes of their paintings. Among the Indonesian artist especially at Bandung city, which's raised that tradition themes is Haryadi Suadi and Radi Arwinda. Both of them are nearest relation and have Cirebon culture background which's have relation as a father and son. In this study, author illuminate the paintings visualisation created by Haryadi and Radi, as well as examine the aesthetic value which's consist in it. This study have the purpose for knowing visual value, theme and meaning of symbol, showing objects, technique and media which's used, as well as painting style which's out warded by of both that artist. Data was collected with observation techniques, interview, documentation, and literature study. The next stage, author analyze the aesthetic study of paintings Haryadi and Radi. Analysis process is doing with nearing aesthetic approach and comparison study. After seeing the analysis result, author can take the red yarn of this research. Haryadi and Radi have same academic background of Fine Art at FRSD ITB. Although both of them different generation, but both of paintings have the special charactheristic of Cirebon which's strong. Haryadi's painting still consist in a modern art, whereas Radi following the contemporary art. Either Haryadi or Radi have the same themes of folklore in their painting. Haryadi's painting are divided into four themes, namely the Javanese puppets figure, supranatural being, Jayabaya forecast, and Chinese Primbon. While that Radi's painting divided into four themes, namely the Javanese puppet figure, supranatural being, worship being, and Japanese Maneki Neko. Haryadi's painting style tends expressionist while Radi featuring the pop art style and decorative. The result of this study expect can be the reference for art connoisseur as an apreciation reference as well as give the inspiration and the idea for the other researcher. For the artist which's studied, hopefully they motivated for do always the creative process and work better until can be the historical record as well as enriching the treasures of Indonesian painting.